Renegotiating Nonresidential Father–Child Relationships During Emerging Adulthood. Issue 5 (December 2016) - Feistman, Richard; Jamison, Tyler; Coleman, Marilyn; Ganong, Lawrence
Abstract : Father–child relationships tend to decrease in quality and closeness following parental divorce, yet little is known about how these relationships evolve in response to normative developmental changes in children. We conducted a grounded theory study of how 33 emerging adults maintained or changed their relationships with their nonresidential fathers during the transition to adulthood. In‐depth interviews revealed that some father–child relationships were unchanged by divorce, but most became more distant immediately following parental separation. During emerging adulthood these relationships did not necessarily become closer, but communication often increased and stressful interactions decreased for some, especially when compared to childhood. The findings suggest that normative changes that accompany emerging adulthood (e.g., leaving home, gaining new insight about themselves and their families) may facilitate renewed connections between previously distant nonresidential fathers and children.